2022
DOI: 10.1155/2022/9611362
|View full text |Cite
|
Sign up to set email alerts
|

Periodontopathic Microbiota and Atherosclerosis: Roles of TLR-Mediated Inflammation Response

Abstract: Atherosclerosis is a chronic inflammatory disease with a high prevalence worldwide, contributing to a series of adverse cardiovascular and cerebrovascular diseases. Periodontal disease induced by pathogenic periodontal microbiota has been well established as an independent factor of atherosclerosis. Periodontal microorganisms have been detected in atherosclerotic plaques. The high-risk microbiota dwelling in the subgingival pocket can stimulate local and systematic host immune responses and inflammatory cascad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 93 publications
0
10
0
5
Order By: Relevance
“…Os principais resultados dos 25 artigos selecionados estão presentes no quadro 1. Dentre esses artigos, 8 concordam que a doença periodontal tem papel relevante para doenças cardiovasculares (Bale, Doneen, Vigerust, 2017;Ghizoni et al, 2012, Ghobadi, 2018Łysek et al, 2018;Schenkein et al, 2020;Sen et al, 2018;Sen et al, 2021;Zou et al, 2022). De uma forma geral, é possível observar que a microbiota periodontal patogênica exerce um papel crítico para aumento de mecanismos inflamatórios e progressão das doenças cardiovasculares.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Os principais resultados dos 25 artigos selecionados estão presentes no quadro 1. Dentre esses artigos, 8 concordam que a doença periodontal tem papel relevante para doenças cardiovasculares (Bale, Doneen, Vigerust, 2017;Ghizoni et al, 2012, Ghobadi, 2018Łysek et al, 2018;Schenkein et al, 2020;Sen et al, 2018;Sen et al, 2021;Zou et al, 2022). De uma forma geral, é possível observar que a microbiota periodontal patogênica exerce um papel crítico para aumento de mecanismos inflamatórios e progressão das doenças cardiovasculares.…”
Section: Resultsunclassified
“…É evidente que existe uma relação entre a DP e as DCs. No entanto, como afirmado pelos autores, são necessários mais estudos controlados para que seja estabelecida uma relação de causalidade (Aarabi et al, 2015;Zou et al, 2022).…”
Section: Silva E Deunclassified
“…Meanwhile, TLR4 involves both the MyD88-dependent and TRIF-dependent pathways. Excessive TLR-mediated pathway activation can lead to inflammation and TLR-related diseases. , Recently, several studies have demonstrated that TLR-mediated pathways play crucial roles in macrophage polarization and NLRP3 inflammasome activation, consequently producing inflammatory cytokines and causing inflammation. , …”
Section: Introductionmentioning
confidence: 99%
“…To date, more than ten types of TLRs have been found in mammals [ 13 , 14 ]. TLRs are associated with the development and instability of cardiovascular disease and cancer [ 15 17 ]. The TLR protein is a single transmembrane noncatalytic protein that has a conservative molecular structure.…”
Section: Introductionmentioning
confidence: 99%